An embedded Chiasm in the narrative structure of Psalm 105 - Martin, Lee Roy (Journal for Semitics, 2019)
This article suggests that a previously unrecognised chiasm is embedded within the narrative structure of Psalm 105. Both the narrative structure and the chiastic structure of Psalm 105 are described, and the rhetorical significance of these structures is explored. The narrative structure points to the value of historical recital as a form of testimony and theological articulation within the liturgical life of Israel. The chiastic structure highlights significant elements of the psalm and its story. The emphasis of Psalm 105 is on Yahweh’s power and dominance over Israel’s enemies, a dominance that generates trust and hope that would be particularly beneficial to those hearers who were suffering in the exilic or in postexilic contexts.
free
Keywords: Chiasm; Historical recital; Psalms; Testimony; Transitioning